Case series of sporotrichosis at a teaching hospital in Brazil - Benvegnú,Ana Maria (2020)
Abstract INTRODUCTION: Sporotrichosis is a subcutaneous fungal infection with a worldwide distribution and higher incidence in tropical and subtropical areas, such as the Brazilian territory, where it has been standing out due to its frequent epidemics. Thus, the present study aimed to evaluate the prevalence of sporotrichosis and profile the affected patients at a university teaching hospital in the central region of Rio Grande do Sul, Brazil. METHODS: This study was a case series of patients diagnosed with Sporothrix spp. from January 2006 to December 2015 by microscopic examination or fungal isolates. Medical records were reviewed for epidemiological data. RESULTS: Forty-three cases of sporotrichosis were diagnosed through the period. The sample comprised predominantly young male adults and rural workers. The most common disease type was lymphocutaneous (51%), followed by fixed cutaneous form (32.5%). The predominant location was the upper limbs (70%), followed by the lower limbs (16%). A significant association was observed between the lymphocutaneous form and upper limb location and between the fixed cutaneous form and lower limb location (p = 0.019). Potassium iodine and itraconazole were the most common treatments. CONCLUSIONS: This study will help update the epidemiological situation of sporotrichosis in the central region of the state of Rio Grande do Sul, Brazil, over the last decade.